Uji Daya Hambat Antibakteri Produk Sabun Cuci Tangan Ekstrak Kulit Kakao (Theobroma cacao L.) Pada Bakteri Patogen - Dewi, Annisa Mulya; Priantari, Ika; Munandar, Kukuh (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to explore the effectiveness of handwashing soap made from cocoa pod husk extract in inhibiting the growth of pathogenic bacteria such as Salmonella typhi, Staphylococcus aureus, and Escherichia coli, which are common causes of various diseases. The extract used was a crude cocoa pod husk extract obtained through the maceration method using distilled water (aquadest) as the solvent. The extract was then formulated into soap at concentrations of 80%, 90%, and 100%. Antibacterial activity tests were carried out using the disk diffusion method based on CLSI standards to measure the inhibition zones against Escherichia coli, Staphylococcus aureus, and Salmonella typhi. The study used a completely randomized factorial design (3 x 3), involving three extract soap concentrations and three types of bacteria, each tested in three replications. Data were analyzed using Analysis of Variance (ANOVA) to determine the significance of differences among treatments. The inhibition zone measurements showed that at concentrations of 80%, 90%, and 100%, the zones for E. coli were 4.1 mm, 4.9 mm, and 6.3 mm respectively, classified as weak to moderate. For S. aureus, the inhibition zones were 7.3 mm at 80%, 11.30 mm at 90%, and 13.77 mm at 100%, which fall into the moderate to strong category. For S. typhi, the inhibition zones were 5.16 mm (80%), 6.3 mm (90%), and 8.81 mm (100%), categorized as moderate. It can be interpreted that cocoa pod husk extract soap showed the most effective antibacterial activity against S. aureus at 90% and 100% concentrations, while its inhibitory effect on E. coli and S. typhi was weaker to moderate. Biologically, the effectiveness of cocoa pod husk extract soap as a natural antibacterial agent is more optimal against Gram-positive bacteria such as S. aureus, whereas its effectiveness against Gram-negative bacteria like E. coli and S. typhi still needs to be optimized. The ANOVA test results showed a p-value < 0.05, indicating that the average inhibition zone results among the three bacterial types differed significantly. This confirms the potential of cocoa pod husk as a natural raw material for producing environmentally friendly antibacterial hand soap.